Polypropylene composite material as well as preparation method and application thereof
By adding EAA and tackifying resin to the polypropylene composite material, the problem of poor compatibility when blending PP and PET is solved, and the mechanical properties and stability of the material are significantly improved.
Patent Information
- Application Number
- CN202411988114.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
When blending, PP and PET are difficult to form a uniform phase structure due to differences in polarity and molecular structure, and have poor compatibility, which affects the mechanical properties and stability of the material.
By adding ethylene-acrylic acid copolymer (EAA) with certain polar groups and a tackifying resin, EAA forms hydrogen bonds or polar interactions with PET, improving the compatibility between PP and PET, and the tackifying resin promotes uniform dispersion and fusion of the two phases, inhibiting the formation of a multiphase morphological structure.
The compatibility of PP resin and PET resin is significantly improved, the mechanical properties of polypropylene composite materials are improved, such as the tensile strength of weld marks and tensile creep properties, and the stability of the material is enhanced.
Smart Images

Figure BDA0005223048590000061 
Figure BDA0005223048590000071 
Figure BDA0005223048590000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a polypropylene composite material and a preparation method and application thereof. Background Art
[0002] Polypropylene (PP) and polyethylene terephthalate (PET) are two common thermoplastics, each with unique properties. As a thermoplastic, PP is widely used in many fields due to its advantages such as light weight, high strength, wear resistance, chemical resistance and thermal stability. PET is a milky white or light yellow highly crystalline polymer with a smooth and shiny surface, good creep resistance, fatigue resistance, abrasion resistance and dimensional stability, and low gas and water vapor permeability. Blending PP with PET aims to combine the advantages of both and create a composite material with higher comprehensive performance.
[0003] However, there are significant differences in polarity and molecular structure between PP and PET, which becomes a major challenge in the blending process of the two. PP is a non-polar polymer, and its molecular chain is mainly composed of non-polar propylene units; while PET is a polar polymer, and its molecular chain contains polar groups. This difference makes it difficult for the two to form a uniform phase structure when mixed, and the compatibility is poor. After blending, it is easy to form a multiphase morphological structure, which not only affects the mechanical properties of the material, but may also cause the material to phase separate after long-term use or environmental changes, thereby reducing the stability of the material.
[0004] Therefore, a polypropylene composite material with high weld mark tensile strength, good tensile creep performance, and long environmental stress cracking resistance time has broad application prospects. Summary of the invention
[0005] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a polypropylene composite material with high weld mark tensile strength, good tensile creep performance, and long environmental stress cracking resistance time, as well as a preparation method and application thereof.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is: a polypropylene composite material, comprising the following components in parts by weight: 65-85 parts of PP resin, 5-10 parts of PET resin, 3-8 parts of ethylene-acrylic acid copolymer (EAA), and 3-8 parts of tackifying resin.
[0007] The present invention adds EAA having certain polar groups and having interfacial wetting and bridging effects. On the one hand, the acrylic acid group in the EAA molecular structure can form a hydrogen bond with the ester group of PET or interact through polarity, thereby forming a stable bond at the interface between PP and PET, thereby improving the compatibility between the two. EAA itself also has good compatibility and can be evenly dispersed in the PP matrix. On the other hand, EAA has good processing performance, can maintain stable performance within a wide processing temperature range, and is not prone to adverse reactions such as degradation or cross-linking. At the same time, the addition of the tackifying resin can, on the one hand, effectively insert between the molecular chains of PP and PET, and can also effectively insert between the molecular chains of EAA, so that a stable interaction force is formed as a whole; on the other hand, through its unique viscoelastic behavior, it promotes the uniform dispersion and fusion of the two phases during the blending process, effectively inhibiting the formation of a multiphase morphological structure.
[0008] The present invention significantly improves the compatibility of PP resin and PET resin by combining EAA and tackifying resin, thereby improving the mechanical properties of the polypropylene composite material, such as weld mark tensile strength and tensile creep performance, and further improving the stability of the polypropylene composite material.
[0009] Preferably, the weight percentage of the PP resin in the polypropylene composite material is not less than 60%.
[0010] Preferably, the mass percentage of acrylic acid in the ethylene-acrylic acid copolymer is 4-15%.
[0011] Preferably, the weight ratio of the ethylene-acrylic acid copolymer to the tackifying resin is 1:(1-1.2).
[0012] The inventors found in actual experiments that when the weight ratio of EAA to the tackifying resin is within the above range, the tackifying resin can be better inserted between EAA molecules, and the mechanical properties and stability of the polypropylene composite material are better.
[0013] Optionally, the weight of the PP resin is in the range of 65, 68, 70, 72, 75, 80, 82, 85 parts or any two of the range values; the weight of the PET resin is in the range of 5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 parts or any two of the range values; the weight of the EAA is in the range of 3, 3.5, 4, 4.5, 5, 6, 6.5, 7, 7.5, 8 parts or any two of the range values; the weight of the tackifier resin is in the range of 3, 3.5, 4, 4.5, 5, 6, 6.5, 7, 7.5, 8 parts or any two of the range values.
[0014] Preferably, the melt flow rate of the PP resin at 230° C. and 2.16 kg according to ISO 1133-1-2022 is 0.5-30 g / 10 min, the intrinsic viscosity of the PET resin is 0.5-0.8 dL / g, and the intrinsic viscosity of the PET resin is obtained by testing according to GB / T 14190-2017.
[0015] Preferably, the ethylene-acrylic acid copolymer has a melt flow rate of 2.5-10 g / 10 min at 190° C. and 2.16 kg according to ISO 1133-1-2022.
[0016] Further preferably, the ethylene-acrylic acid copolymer has a melt flow rate of 7-8 g / 10 min at 190° C. and 2.16 kg according to ISO 1133-1-2022.
[0017] The inventors found in the actual experimental process that when the EAA melt flow rate is 2.5-10g / 10min, the system compatibility is improved and the interface bonding is better, so that the polypropylene composite material has better mechanical properties and stability. When the EAA melt flow rate is 7-8g / 10min, the moderate melt flow rate corresponds to a more appropriate molecular chain length and branching degree, so that EAA has better molecular chain entanglement and interaction while maintaining a certain fluidity, thereby making the mechanical properties and environmental stress cracking resistance of the polypropylene composite material better.
[0018] Optionally, the melt flow rate of the PP resin at 230°C and 2.16 kg according to ISO 1133-1-2022 is 0.5 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 7.5 g / 10 min, 8 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min or any two of the range values; the intrinsic viscosity of the PET resin is 0.5 dL / g, 0.6 dL / g, 0.7 dL / g, 0.8 dL / g or any two of the range values; the ethylene-acrylic acid copolymer ... The melt flow rate of 1133-1-2022 at 190°C and 2.16 kg is in the range of one or any two of 2.5 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 7.5 g / 10 min, 8 g / 10 min, and 10 g / 10 min.
[0019] Preferably, the tackifying resin is at least one of rosin resin, petroleum resin and terpene resin.
[0020] Preferably, the tackifying resin has a softening point of 80-120°C.
[0021] Further preferably, the softening point of the tackifying resin is 80-100°C.
[0022] Preferably, the softening point of the tackifying resin is based on the ring and ball method in GB / T 2294-97 "Determination of softening point of coking solid products".
[0023] The inventors found in the actual experimental process that the tackifying resin with a softening point of 80-120°C can quickly soften and evenly disperse at an appropriate temperature, so that it can be more evenly dispersed in the polypropylene matrix, achieving the combination of various components, and the system compatibility is good. The interaction force between the tackifying resin with a softening point of 80-120°C and the PP molecular chain is moderate, which can enhance the adhesion without causing excessive phase separation, thereby ensuring that the polypropylene composite material has excellent mechanical properties and stability. When the softening point of the tackifying resin is 80-100°C, the moderate movement of the tackifying resin molecular chain allows the material to undergo a certain deformation when subjected to tensile stress without being easily broken, thereby further improving the mechanical properties and environmental stress cracking resistance of the material.
[0024] Optionally, the tackifying resin has a softening point in the range of one or any two of 80°C, 90°C, 95°C, 100°C, 115°C, and 120°C.
[0025] Preferably, the polypropylene composite material further comprises 0.5-5 parts of filler and 0.5-5 parts of processing aid; the filler is at least one of talcum powder, barium sulfate and calcium carbonate, and the processing aid is at least one of a nucleating agent and a lubricant.
[0026] Optionally, the mesh size of the filler is 1250-2500 mesh.
[0027] Optionally, the weight portion of the lubricant is 0.5-2.5 parts, and the lubricant is at least one of stearates, stearic acid esters, and ethylene bis stearic acid amides, such as pentaerythritol stearate, zinc stearate, and the like.
[0028] Optionally, the weight portion of the nucleating agent is 0.5-2.5 parts, and the nucleating agent is a β-crystal nucleating agent.
[0029] In addition, the present invention provides a method for preparing the polypropylene composite material, comprising the following steps: mixing the components in proportion, and then melt-extruding and granulating to obtain the polypropylene composite material.
[0030] Preferably, the extrusion temperature of the twin-screw extruder is 200-250°C.
[0031] Furthermore, the present invention provides application of the polypropylene composite material in the automotive field.
[0032] Specifically, the present invention provides the use of the polypropylene composite material in the preparation of automobile blower impellers and automobile cooling fans.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention significantly improves the compatibility of PP resin and PET resin by combining EAA and tackifying resin, thereby improving the mechanical properties of the polypropylene composite material and further improving the stability of the polypropylene composite material. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.
[0035] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:
[0036] PP resin-1: homopolymer PP, melt flow rate 0.5g / 10min (230℃ / 2.16kg), B1101, Formosa Chemical Corporation;
[0037] PP resin-2: homopolymer PP, melt flow rate 12g / 10min (230℃ / 2.16kg), HP500N, CNOOC Shell;
[0038] PP resin-3: homopolymer PP, melt flow rate 30g / 10min (230℃ / 2.16kg), brand J-3000GP, Pu Ruiman;
[0039] PET resin-1: intrinsic viscosity 0.52dL / g, CR-7702, Sinopec;
[0040] PET resin-2: intrinsic viscosity 0.68dL / g, FG600, Sinopec;
[0041] PET resin-3: intrinsic viscosity 0.8dL / g, BG80, Sinopec;
[0042] EAA-1: melt flow rate is 5g / 10min (190℃ / 2.16kg), brand 1430, manufacturer DuPont, USA;
[0043] EAA-2: melt flow rate is 7g / 10min (190℃ / 2.16kg), brand 30707, manufacturer DuPont, USA;
[0044] EAA-3: melt flow rate is 8.2g / 10min (190℃ / 2.16kg), brand Escor TM 5000, manufacturer: ExxonMobil, USA;
[0045] EAA-4: melt flow rate is 2.6g / 10min (190℃ / 2.16kg), brand PRIMACOR TM 1321, manufacturer: SK Korea;
[0046] EAA-5: melt flow rate is 10g / 10min (190℃ / 2.16kg), brand 3990, manufacturer DuPont, USA;
[0047] Tackifying resin-1: water-based rosin resin, softening point 82°C, Yoshida Chemical;
[0048] Tackifying resin-2: 95# rosin resin, softening point 95℃, Eastman;
[0049] Tackifying resin-3: petroleum resin, softening point 85°C, brand FST-C90, manufacturer Hengfeng Petrochemical;
[0050] Tackifying resin-4: polymerized rosin 115, softening point 115℃, Yoshida Chemical;
[0051] Talc: 2500 mesh talc, commercially available;
[0052] Nucleating agent: β-crystal nucleating agent TMB-5, Shanxi Chemical Research Institute;
[0053] Lubricant: Zinc stearate, commercially available.
[0054] Examples 1-14 and Comparative Examples 1-5
[0055] The components and weight proportions of the polypropylene composite material of the present invention are shown in Table 1-Table 2. The preparation method of the polypropylene composite material of the present invention comprises the following steps: mixing the components in proportion and then feeding them into a twin-screw extruder for processing, and obtaining the polypropylene composite material through extrusion, cooling and granulation; the extrusion temperature of the twin-screw extruder is 200-250°C, wherein the first section is 200°C, the second to fourth sections are 250°C, the fifth to eighth sections are 240°C, and the ninth section of the die head is 230°C.
[0056] Performance Testing
[0057] Weld mark tensile strength: refer to ISO 527-1-2012 standard, injection mold ISO 1A dumbbell tensile specimen, the molding mold is double-sided hedging welding injection molding, after injection molding, adjust in standard environment for 48 hours, use 50mm / min speed to perform tensile test, and record the tensile strength.
[0058] Tensile creep test: Equipment manufacturer: Coesfeld, Germany, force sensor range: 10kN, 1kN; force sensor accuracy: ±0.02%, stepper motor: 0.072° / step, 5000 steps for one rotation of 360°; stepper motor accuracy: 0.05μm.
[0059] Test method: Step 1: Use ISO mechanical 1A tensile specimen to test the static tensile strength at 80°C; Step 2: Calculate 80% of the static tensile strength at 80°C as the tensile creep set load; Step 3: Set the temperature of the environmental chamber to 80°C, and place the specimen in the creep environmental chamber for 4 hours; Step 4: Fixture the tensile specimen, and start the tensile creep test after the force is reset to zero; Step 5: Observe the rupture time of the equipment, conduct the test until the specimen breaks, and record the creep rupture time.
[0060] Environmental stress cracking resistance test: The test standard is ASTM D1693-2015, the test temperature is 30°C, and the test medium is 10% nonylphenol polyoxyethylene ether (TX10). The longer the environmental stress cracking resistance time, the better the environmental stress cracking resistance.
[0061] The performance test results are shown in Table 1-Table 2.
[0062] Table 1
[0063]
[0064]
[0065]
[0066] Table 2
[0067] project Comparative Example 1 Comparative Example 2 PP resin-1 75 75 PET resin-1 8 8 EAA-1 0 11 EAA-4 0 0 EAA-5 0 0 Tackifying resin-1 11 0 Tackifying resin-4 0 0 talcum powder 3 3 Nucleating Agent 2 2 Lubricants 2 2 Weld line tensile strength (MPa) 28.2 29.3 Tensile creep (h) 84 79 Environmental stress cracking resistance time (h) 105 96
[0068] It can be seen from the above table that the tensile strength of the weld mark of the polypropylene composite material prepared in the embodiment of the present invention is ≥30 MPa, the tensile creep is ≥110h, and the environmental stress cracking resistance time is ≥230h.
[0069] From the comparison of Examples 1-5, it can be seen that when the melt flow rate of the PP resin is 0.5-30 g / 10 min and the intrinsic viscosity of the PET resin is 0.5-0.8 dL / g, a polypropylene composite material with high weld mark tensile strength, good tensile creep performance and long environmental stress cracking resistance time can be obtained.
[0070] From the comparison between Example 1 and Examples 6-9, it can be seen that when the EAA melt flow rate is 2.5-10 g / 10 min, the system compatibility is improved, and the interface bonding is better promoted, so that the polypropylene composite material has better mechanical properties and stability. When the EAA melt flow rate is 7-8 g / 10 min, a polypropylene composite material with higher weld mark tensile strength, better tensile creep performance, and longer environmental stress cracking resistance time can be obtained.
[0071] By comparing Example 1 and Examples 10-12, it can be seen that the tackifying resin with a softening point of 80-120°C can be quickly softened and evenly dispersed at an appropriate temperature, so that it can be more evenly dispersed in the polypropylene matrix, achieving the combination of various components, and the system compatibility is good, so that the polypropylene composite material has better mechanical properties and stability. When the softening point of the tackifying resin is 80-100°C, a polypropylene composite material with higher weld mark tensile strength, better tensile creep performance, and longer environmental stress cracking resistance time can be obtained.
[0072] From the comparison of Example 1, Examples 13-17, and Comparative Examples 1-2, it can be seen that when the weight ratio of the ethylene-acrylic acid copolymer to the tackifying resin is 1:(1-1.2), a polypropylene composite material with higher weld mark tensile strength, better tensile creep performance, and longer environmental stress cracking resistance time can be obtained.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composite material, characterized in that: The invention comprises the following components in parts by weight: 65-85 parts of PP resin, 5-10 parts of PET resin, 3-8 parts of ethylene-acrylic acid copolymer and 3-8 parts of tackifying resin.
2. The polypropylene composite material according to claim 1, characterized in that The weight ratio of the ethylene-acrylic acid copolymer to the tackifying resin is 1:(1-1.2).
3. The polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the PP resin under the conditions of 230° C. and 2.16 kg according to ISO 1133-1-2022 is 0.5-30 g / 10 min, and the intrinsic viscosity of the PET resin is 0.5-0.8 dL / g.
4. The polypropylene composite material according to claim 1, characterized in that: The ethylene-acrylic acid copolymer has a melt flow rate of 2.5-10 g / 10 min at 190° C. and 2.16 kg according to ISO1133-1-2022.
5. The polypropylene composite material according to claim 1, characterized in that: The tackifying resin is at least one of rosin resin, petroleum resin and terpene resin.
6. The polypropylene composite material according to claim 5, characterized in that: The softening point of the tackifying resin is 80-120°C.
7. The polypropylene composite material according to claim 1, characterized in that: The polypropylene composite material further comprises 0.5-5 parts of filler and 0.5-5 parts of processing aid; the filler is at least one of talcum powder, barium sulfate and calcium carbonate, and the processing aid is at least one of a nucleating agent and a lubricant.
8. A method for preparing the polypropylene composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the components in proportion, melting, extruding and granulating to obtain the polypropylene composite material.
9. Use of the polypropylene composite material according to any one of claims 1 to 7 in the automotive field.
10. Use of the polypropylene composite material according to any one of claims 1 to 7 in the preparation of automobile blower impellers and automobile cooling fans.
Citation Information
Patent Citations
High-strength polypropylene (PP) / polyethylene glycol terephthalate (PET) alloy fiber and preparation method thereof
CN103911682A
Polypropylene composition and polypropylene material
CN107312239A
High-performance PP / PET alloy material and preparation method thereof
CN115895121A
Process and apparatus for preparing polyolefin / polyglycol terephthalate in-situ micro-fibril reinforced composite material
CN1346845A
Polypropylene composition
JP1999343372A